Предмет:
МатематикаАвтор:
анонимРешение:
a4 + a2 + 1 + a2 - a2 = (a4 + 2a2 + 1) - a2;
(a2 + 1)2 - a2;
(a2 + 1)2 - a2 = (a2 + 1 – a)(a2 + 1 + a);
a2 – a + 1 = 0;
D = b2 - 4ac = 1 - 4 · 1 · 1= - 3 < 0 => уравнение корней не имеет;
a2 + a + 1= 0;
D = b2 - 4ac = - 3 < 0 => уравнение корней не имеет.
Ответ: a4 + a2 + 1= (a2 – a + 1)(a2 + a + 1).
Автор:
melaniemyersДобавить свой ответ
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть